Increasing Public Interest in Online Education during the COVID-19 Pandemic in the United States: An Analysis of Google Trends Data - Qinyi Tan; Ziqi Zhang; Luyan Teng (Journal of Education, Health and Sport)
Objective: Current evidence suggests that the shift to online learning during the COVID-19 pandemic has profoundly impacted teaching and learning models. This study aims to quantify trends in public interest in different forms of education and associated online search behaviors during the pandemic. Furthermore, it seeks to "nowcast" potential future scenarios concerning the evolution of online education.